PENGARUH MEDIA PRODUK GOOGLE DAN MOTIVASI BELAJAR SISWA SMAN 3 MOJOKERTO - Zainal Abidin; Hartono Hartono; Soegito Soegito (JUPI (Jurnal Pendidikan Indonesia), 2023)
Online learning is a must, because online learning really helps students improve learning outcomes and learning motivation. The research aims to determine learning outcomes and scientific attitudes that are taught using Google Classroom and Google Meet learning media. The population in this study were students of class XIPS SMAN 3 Mojokerto for the 2022/2023 academic year. Sampling was carried out using the Pretest and Post test techniques, the results of data analysis showed that there was an increase in learning outcomes using Google Classroom and Google Meet for 15 students, after receiving pretest and posttest treatment. Students have better grades when the treatment has been carried out compared to before the treatment is carried out, it is concluded that learning outcomes taught using learning motivation media are higher than students taught with google classroom and google meet media. That the influence of learning media with Google classroom and Google meet as relaxation techniques is 80%, effective for students of SMAN 3 Mojokerto majoring in social sciences in learning Physics on Newton's Laws